Enhancing clay soil stability in seasonal freezing areas through waste cherry marble powder and geotextile reinforcement - Odemis, Muhammet Nuri; Firat, Muge Elif (Elsevier Sci Ltd, 2024)
In this study, the mechanical and durability performance of clay soils reinforced with different proportions of Cherry Marble Powder (CMP) and non-woven geotextile configurations, both independently and in combination, is investigated in detail at both the macro and micro levels. The effectiveness of reinforcement in the stabilization of clay soils in cold climates has been evaluated by means of Gray Correlation Analysis (GCA). The results show that as the CMP ratio and the number of geotextiles increase, the peak strength of the soil increases, with higher CMP levels showing perfect plastic behavior and more geotextiles showing linear strain hardening, particularly in combination. Substantial strength reductions post-7th cycle ranged between 91.09 % and 103.38 % for 12 % CMP and 219.83 % and 270.42 % for three-layered geotextile groups. Cohesion increased by 59.76 % and 179.41 %, while the internal friction angles remained stable and decreased after F-T cycles, except with additives. Failure modes shifted with CMP content, F-T cycles and confining pressure. The transition was from strain hardening to strain softening, with increased shear fracture planes and brittleness. The energy absorption capacity (EAC) increased with the CMP ratio, with the geosynthetic reinforcement increasing the EAC by a factor of 1.5 before and after the F-T cycles. The combined use of CMP and geotextiles in soil stabilization improved the engineering properties in areas of frost, with the optimum gradation being three layers of geotextile and a CMP ratio of 12 %, which effectively mitigated the effects of the maximum F-T cycle.
Keywords: Clay soil; Geotextile; Cherry marble powder; Undrained-unconsolidated triaxial behavior; Freeze -thaw cycles